Pengaruh Internet Banking Terhadap Kinerja Perbankan di Indonesia (Studi Empiris Pada Bank yang Listing di BEI) - Ronaldo Egan; Hudi Prawoto (Jurnal Akuntansi Bisnis, 2013)
This study aimed to determine the effect of internet banking on banks' performance, in term of earning. Based on the analysis and discussion in the previous section, it can be concluded that results of this study show empirical evidence that the application of internet banking brings negative and significant effect on the growth of public bank earnings who use internet banking in Indonesia, based on financial statements in 2002 through 2011. The study also examines banking ratio such as size, capital, credit risk, expense management, liquidity and the two macro economic factors, namely inflation and economic growth on earnings. The stated ratio, such as size, capital, credit risk, expense management, inflation, economic growth and significant effect on earnings. For size and capital, those ratios bring positive and significant effect on earnings, while credit risk, expense management, inflation, a significant negative effect economic growth on earnings. In this study, liquidity variable brings non-significant positive effect on earnings.